PENGEMBANGAN LECTORA INSPIRE SEBAGAI MULTIMEDIA INTERAKTIF PEMBELAJARAN KIMIA PADA POKOK BAHASAN HIDROLISIS GARAM DI SMA/MA - Sellyna, Novia; M. Noer, Asmadi; Linda, Roza (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The design research of Lectora Inspire Interactive Multimedia for Salt Hydrolysis subject in aims to get a valid and practical material learning. The research method in the Design Research with Plomp model through five phases are: Prelimery Investigation phase; phase Design; Realization phase; Test, Evaluation, and Revision phase; and Implementation phase. The research was conducted through the Test, Evaluation, and Revision phase. Data collect technique by validating Interactive Multimedia Lectora Inspire to three people validator (media expert and matter experts) and the trials of Interactive Multimedia Lectora Inspire had done by practitioners (users). Limited trial subjects are three teachers SMA/MA and 15 students from class XI. Data analysis technique was used descriptive analysis percentage. The research results show percentage score the designing aspect 96.8%; pedagogic aspects 96.8%; the content aspects 95.05%; the ease of use aspects 95.8%, teachers response 98.3%; and the learners response 94.7%. Average score overall validation of Interactive Multimedia Lectora Inspire on the Salt Hydrolysis subject is 96.05% including valid category and the average score overall response practitioners is 96.5% including practical criteria and can be used on the salt hydrolysis subject in class XI SMA / MA.Keywords: Interactive Multimedia, Lectora Inspire, Salt Hydrolysis